Freistellung von Betriebsräten - Eine Beschäftigungsbremse? - Lena Koller; Claus Schnabel; Joachim Wagner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– According to the German Works Constitution Act, establishments whose workforces exceed certain thresholds have to release a certain number of members of their works councils from their regular work and enable them to work full time as works councillors. Using a full sample of all establishments affected, we analyse whether making provision for the first full-time works councillor dampens employment growth. We also investigate whether the change in the threshold value from 300 to 200 employees that came into effect in July 2001 had any impact on employment growth at these thresholds. Both descriptive and econometric analyses suggest that neither the old nor the new threshold value has affected establishments' employment growth. The same holds for the legal reform of this threshold value.
Keywords: 330; Betriebsverfassungsgesetz - Reform; Reformpolitik - Auswirkungen; Betriebsgröße; Betriebsrat; Freistellung; Kosten; Beschäftigungseffekte; IAB-Betriebs-Historik-Panel